Harnessing Diversity: The Role of Inclusive HR Practices in Driving Innovation and Organizational Growth - Qurniawan, Hendry; Saragihi, Ilham Syahputra; Suhendro, Dedi (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study explores the impact of inclusive human resource practices and workforce diversity on organizational growth, with a focus on the mediating role of innovation capability. Using data from Balai Pengelola Transportasi Darat Kelas II Provinsi Sumatera Barat, the research employs a quantitative design with random sampling, resulting in 78 respondents from a population of 352. Path analysis, conducted using SmartPLS, reveals significant direct and indirect effects of inclusive human resource practices and workforce diversity on organizational growth, mediated through innovation capability. Inclusive human resource practices significantly enhance innovation capability, which in turn drives organizational growth. Similarly, workforce diversity contributes to organizational growth by improving innovation capabilities. These findings highlight the importance of fostering an inclusive and diverse work environment to promote innovation and achieve sustainable organizational success.